O conselho escolar e a eleição de diretores como elementos do modelo de gestão democrática - Oliveira, Francisco José Machado de (2005)
This study discusses about the school council and the election of principals as main elements of a democratic model of management. The question to be answered is related to factors that help or difficult the process of implementation and functioning of the school council in a state public school in Fortaleza. Its objective is to analyze and explain the work done by the “Centro de Atenção Integral à Criança e ao Adolescente (CAIC) Maria Felício Lopes” which includes the whole school community. It is important to mention that this is manly an analytical study of an exploratory case, whose results can be measured and used for further analysis. The investigation phase allowed to get knowledge of the subject matter mainly obtained trough questionnaires and interviews focused on school community formed by students, parents or sponsors, teachers, employees, board members and members of academic council. Data on such investigation were analyzed based on the descriptive statistics. This study attempts to contribute to the understanding of the academic council, the election of principals and the democratic management process. Authors like Demo, Freire, Gadotti, Hora, Lück, Paro, Saviani, Vieira and others were of extreme importance as theoretical bases. A total of five assumptions were considered for this work, where the first three reveled to be completely truthful, the fourth one was partially truthful and the fifth one has proved to be false. Outcomes showed that the following assumptions were truthful: the school community knows in part what the importance is and what the responsibilities are to be executed by the academic council; the lack of experience on how to combine and work with groups impedes the participation of community member in the democratic council and a lack of a team work attitude and knowledge translates into a nonparticipation in the academic council process. It was partially truthful the assumption: the school community does not recognize the necessity of a participation needed in the process of democratic council. The assumption: the academic council in already involved in all the important decision to be made by the school was considered false. This study permitted to conclude , based on the established objectives, that the CAIC Maria Felício Lopes does not have yet a complete democratic management process, since members of the school community do not know the functions of the school council. Beyond that, members of the community do not demonstrate to be interested in participating on action developed by the mentioned council. Outcomes shown the necessity of changes in the democratic model of management of the school, in which must be introduced new mechanisms of articulation between the school groups in order to achieve participation and efficacy on the management process.